Current Status and Future Prospects for Electronic Point-of-Care Clinical Decision Support in Diabetes Care - O’Connor, Patrick J. (2013)
Early efforts to use point-of-care clinical decision support (CDS) were limited to the use of prompts and reminders, which improved test ordering but not intermediate outcomes of care such as glucose, blood pressure, or lipid levels. More sophisticated diabetes CDS tools are now available that use electronic medical record data to provide patient-specific advice on medication use based on previous treatment, distance from goal, and other clinical data. These tools have shown modest but significant improvement in glucose and blood pressure control. Promising next-generation developments will include prioritizing clinical actions that have maximum benefit to a given patient at the point of care and developing effective methods to communicate CDS information to patients to better incorporate patient preferences in care decisions.